Universities e-Leadership on Virtual Learning. A Case of University of Nairobi, Kenya - Nyaegah, John (African Journal of Education and Practice, 2024)
Purpose: The purpose of this study was to assess the role of e-Leadership in providing Virtual Education. Methodology: The research methodology used in this paper was Desktop Review commonly referred to as secondary data which basically collects data from the existing reference materials most preferably because of its affordability compared to a field research. The study focused mainly on published studies and reports which were accessed through online journals and also libraries. Findings: To successfully establish and implement virtual learning programs in universities, a focused, sound and clear e-leadership is very critical. Besides, the University of Nairobi needs to urgently put plans in place for building a resilient e-Leadership system that will enhance effective skill development for e-service delivery, and productivity among students.In order to standardize and ensure high quality education, virtual learning training sessions are needed so as to boost e-learning standards in the university. Unique Contribution to Theory, Practice and Policy: The study applied Diffusion of Innovation framework which helps leaders and classroom instructors to understand various ways modern technology is used to support instruction and bring about effective content delivery. Based on Diffusion of Innovation Theory, the study encourages educators to continuously improve their mindsets and continually focus on their own self-assessment and their adaptation to new innovations. Change Management Models and Diffusion of Innovation theory were used to justify existing synergy in universities, their leadership and Virtual Education Programs that are aimed at enhancing lecturers’ practical and theoretical training. The study helps to equip classroom instructors with needed skills for incorporating modern technology in their physical and virtual classrooms effectively with a continuous enhancement of their teaching and learning experiences. This study supports policy development which mandates continuous professional development. It is hoped that the literature of this paper will shape and guide academic discourse on e-Leadership concept with a view to understanding the applicability of the concepts and challenges provided for effective adoption.